Cellular prion protein and NMDA receptor modulation: protecting against excitotoxicity - Black, Stefanie A. G.; Stys, Peter K.; Zamponi, Gerald W.; Tsutsui, Shigeki (Frontiers in Cell and Developmental Biology, 2014)
Although it is well established that misfolding of the cellular prion protein (PrPC) into the beta-sheet-rich, aggregated scrapie conformation (PrPSc) causes a variety of transmissible spongiform encephalopathies (TSEs), the physiological roles of PrPC are still incompletely understood. There is accumulating evidence describing the roles of PrPC in neurodegeneration and neuroinflammation. Recently, we identified a functional regulation of NMDA receptors by PrPC that involves formation of a physical protein complex between these proteins. Excessive NMDA receptor activity during conditions such as ischemia mediates enhanced Ca2+ entry into cells and contributes to excitotoxic neuronal death. In addition, NMDA receptors and/or PrPC play critical roles in neuroinflammation and glial cell toxicity. Inhibition of NMDA receptor activity protects against PrPSc-induced neuronal death. Moreover, in mice lacking PrPC, infarct size is increased after focal cerebral ischemia, and absence of PrPC increases susceptibility of neurons to NMDA receptor-dependent death. Recently, PrPC was found to be a receptor for oligomeric beta-amyloid (Abeta) peptides, suggesting a role for PrPC in Alzheimer’s disease. Our recent findings suggest that Abeta peptides enhance NMDA receptor current by perturbing the normal copper- and PrPC-dependent regulation of these receptors. Here, we review evidence highlighting a role for PrPC in preventing NMDA receptor-mediated excitotoxicity and inflammation. There is a need for more detailed molecular characterization of PrPC-mediated regulation of NMDA receptors, such as determining which NMDA receptor subunits mediate pathogenic effects upon loss of PrPC-mediated regulation and identifying PrPC binding site(s) on the receptor. This knowledge will allow development of novel therapeutic interventions for not only TSEs, but also for Alzheimer’s disease and other neurodegenerative disorders involving dysfunction of PrPC.